Analisis Struktur Kepemilikan Perusahaan Terhadap Profitabilitas Perusahaan Makanan dan Minuman yang Terdaftar di BEI - Heni Agustina; Djoko Soelistya (UNUSA Press, 2018)
Abstract: The presence of food and beverage companies currently have an active role in the world economy, where the existence of such companies did not escape from the large number of funding. The funds obtained from some shareholders. Shareholding itself consists of managerial ownership, institutional ownership, and public ownership. This research is quantitative research using observa- tion because it describes the relationships between variables through testing hypothesis. Samples taken from a population with specific criteria. The population in this study i.e. finance report food and beverage companies as much as 70 financial report of the food and beverage companies that are registered in BEI. The results in this study indicates that the managerial ownership variables have no effect on profitability, but institutional ownership and public ownership has an influence on profitability.